Numerical study of detonation initiation by spark discharge in a hydrogen-oxygen high-pressure gas mixture - Korytchenko, K.V.; Martynenko, О.V.; Kasimov, A.M.; Hrytsyna, I.M.; Shevchenko, S.M.; Hrytsyna, N.I. (Problems of Atomic Science and Technology, 2023)
The influence of the initial pressure of the combustible gas mixture on the processes that occur during the initiation of detonation by a spark discharge in a high-pressure hydrogen-oxygen mixture was estimated. A one-dimensional gas-dynamic model in a chemically reacting gas with separation of the vibrational temperature of diatomic molecules from the kinetic temperature of the gas was used for the numerical study. It was simulated that an intensity of the shock wave causing the detonation initiation by a critical regime is below of the detonation wave intensity when the initial gas pressure is 1.013 MPa and the intensity of the shock wave exceeds the detonation wave intensity when the initial gas pressure is 0.304 MPa. It was found out that the process of the detonation initiation falling by a near-critical regime is more longitudinal when the gas pressure is low. Energy deposition history into the spark channel when detonation is initiated at different initial gas pressures was calculated. Оцінено вплив початкового тиску горючої газової суміші на процеси, що відбуваються під час ініціювання детонації іскровим розрядом у воднево-кисневій суміші високого тиску. Для чисельного дослідження використано одновимірну газодинамічну модель у хімічно реагуючому газі з відокремленням коливальної температури двоатомних молекул від кінетичної температури газу. Виявлено, що інтенсивність ударної хвилі, що викликає ініціювання детонації у критичному режимі, є нижчою за інтенсивність хвилі детонації при початковому тиску газу 1,013 МПа, а інтенсивність ударної хвилі перевищує інтенсивність хвилі детонації при початковому тиску газу 0,304 МПа. Встановлено, що процес ініціювання детонації у критичному режимі є більш поздовжнім за низького тиску газу. Розраховано часову залежність вкладення енергії в іскровий канал при ініціюванні детонації за різного початкового тиску газу.